2018
DOI: 10.1136/bcr-2018-224647
|View full text |Cite
|
Sign up to set email alerts
|

SevereBabesia microtiinfection presenting as multiorgan failure in an immunocompetent host

Abstract: A previously healthy 67-year-old farmer presented to an outside hospital after a 2-week history of non-specific respiratory symptoms. A certain diagnosis was not initially apparent, and the patient was discharged home on a regimen for presumed chronic obstructive pulmonary disease exacerbation. He re-presented to the emergency department with shock and hypoxaemic respiratory failure requiring prompt intubation and fluid resuscitation. He was then transferred to our institution due to multiorgan failure. On arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…Both our platforms detected an upregulation of miR-4454, which has been associated with severe thrombocytopenia in P. vivaxinfected human plasma (Santos et al, 2021). Like malaria, babesiosis is also associated with a steep drop in platelets (Akel and Mobarakai, 2017;Ripoll et al, 2018). Furthermore, in our microarray platform, we also found an almost 3.5-fold increase in miR-4497 in iRBC-derived EVs.…”
Section: Discussionsupporting
confidence: 50%
“…Both our platforms detected an upregulation of miR-4454, which has been associated with severe thrombocytopenia in P. vivaxinfected human plasma (Santos et al, 2021). Like malaria, babesiosis is also associated with a steep drop in platelets (Akel and Mobarakai, 2017;Ripoll et al, 2018). Furthermore, in our microarray platform, we also found an almost 3.5-fold increase in miR-4497 in iRBC-derived EVs.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, this review discovered the following less commonly reported sequela or associated conditions: acute lung injury, pulmonary edema, warm autoimmune hemolytic anemia (WAHA) [11], thrombocytopenia [12], reactive hemophagocytosis or hemophagocytic lymphohistiocytosis (HLH) [13], hepatitis [14][15][16], hepatomegaly [14], splenomegaly [14], pancytopenia [17], septic shock [18], multiorgan failure, and even death [12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, there is also a report of a patient whose chronic hepatitis C resolved after co-infection with Babesia, Borrelia burgdorferi, and Ehrlichia (human granulocytic ehrlichiosis) [15]. There was also only one report in which Babesia was involved in septic shock, with other etiologies present [12]. Similarly, the cases involving multiorgan failure involved multiple comorbidities and complicated hospital courses.…”
Section: Multiorganmentioning
confidence: 99%
“…Importantly, the severity of babesiosis is highly dependent on the babesia species (Cooke et al, 2005). For example, babesiosis caused by Babesia microti, B. bovis, B. Lengua, and B. canis is associated with the development of severe syndromes such as brain babesiosis and multi-organ failure due to the sequestration of IEs in the organ's microvasculature (Wright et al, 1979;Aikawa et al, 1992;Bosman et al, 2013;Sondgeroth et al, 2013;Ripoll et al, 2018;Schetters, 2019).…”
Section: Adhesion Of Babesia To the Placentamentioning
confidence: 99%